Classroom research in religious education: The potential of grounded theory - Rothgangel, Martin (HTS teologiese studies, 2017)
Grounded theory is one of the most common qualitative research strategies in social sciences. Currently, many applications of this theory are being developed for religious education. In the article it is argued that grounded theory deserves special attention for classroom research in religious education. For this reason, the basic features (fundamental openness and concurrence of data collection and analysis; constant comparison and asking analytical questions) as well as the coding strategies (open, axial, and selective) of grounded theory will be explained and concretised. An analysis of one example sequence demonstrates how grounded theory may be used to emphasise the communicative and substantive aspects (as well as the interaction between the two) of classroom interaction, therefore lending itself to data analysis. In this manner, grounded theory can also be used for an intensive analysis of a student’s learning process, as the authors have done in one student profile analysis, as well as for a comparative analysis of teaching practice in an actual class or even a variety of classes.